Examining the Impact of Market Reaction Pattern, Managerial Ability, and Corporate Governance on Tax Avoidance in Companies Listed on the Tehran Stock Exchange - Nezhady, Arash; Janani, Mohammad Hasan; Hematfar, Mahmoud; Sefaty, Farid (Management Strategies and Engineering Sciences, 2023)
The primary objective of this study is to examine the impact of the market reaction pattern, managerial ability, and corporate governance on tax avoidance in companies listed on the Tehran Stock Exchange. This research is applied in nature and employs a quasi-experimental, post-event approach within the field of positive accounting research. It utilizes multivariate linear regression and econometric models for analysis. To test the hypotheses, the significance of each regression coefficient was examined using the t-test. The final data analysis was conducted using Excel (2019) and Eviews (10) software. The findings from the hypotheses indicated that tax avoidance has a significant impact on the risk of future stock price crashes. Furthermore, market reaction moderates the impact of tax avoidance, discretionary accruals, and financial constraints on the risk of future stock price crashes. Additionally, managerial ability moderates the impact of financial constraints on the risk of future stock price crashes. Corporate governance moderates the impact of tax avoidance and discretionary accruals on the risk of future stock price crashes. The results showed that managerial ability does not moderate the impact of tax avoidance, discretionary accruals, or financial constraints on the risk of future stock price crashes.